"We are at day one of a new life": translation of a management concept from headquarter to a production team. Issue 7 (7th October 2014) - Rolfsen, Monica; Rolfsen, Monica; Skaufel Kilskar, Stine; Valle, Nina
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to analyze how implementation of a management concept is interpreted by a team within a multinational company. The headquarter "rolls out" a standardized version of teamwork within a lean production system. The authors want to investigate what happens. Design/methodology/approach – The paper is based on a case study approach in a single company with available data over a long period of time. Findings – Instead of being a vehicle for involvement and responsibility through the increased visibility, the tools and techniques become a perceived control mechanism because of a lack of connection between norms and values and tools. Despite the initiating enthusiasm of manager stating that "we are now at day one of a new life", the system is perceived as yet another management concept, and the tools implemented did not represent any meaningful improvement. Research limitations/implications – The paper is based on a single company, describing a particular phenomenon. Practical implications – The paper highlights the importance of involvement when new concepts are transferred into a new social context. Originality/value – The in-depth study of a team within a multinational corporation implementing a management concept is unusual. The main theoretical contribution is to combine conceptualization of both social context and management principles.